GAYA KEPEMIMPINAN CAMAT DALAM MEMPENGARUHI KINERJA PEGAWAI - Deviandi E.42008043, Erik (FISIP Universitas Tanjungpura Pontianak, 2012)
AbstractThis research is intend to know about the leadership style of the leader in improvement of employee’s performance in Ledo Sub-District Office Bengkayang Regency. In this case can be seen that the role and task of the head of Ledo Sub-District is try to affect the employees to keep working effectively in accordance with the time and goals target. In other words, level of employee’s work effectiveness is depend on the way or attitude of the head of sub-district in the lead action or the activities that needed to be done in order to make the employees are willing to follow all of his will to reach the goals of organization.Based on that background, so the formulation of the problem is how the effective leadership style can improvethe employee’s performance in Ledo Sub-District Office Bengkayang Regency. Thus, the goal of this research is to identify and to describe the leadership style of the head of sub-district in improvement of employee’s performance in Ledo Sub-District Office Bengkayang Regency. The research method that used in this research is qualitative descriptive methods and data collection techniques by interview, observation and study documentation. The informant in this research is one main informant and 9 other informants.The conclusion of this research shows that the head of Ledo Sub-district’s leadership style for the present time is not effective yet in implementation, in the meaning of the relationship between the superior and subordinate, from the side of communication, motivation, division of work and giving responsibility, work assessment and leader’s controlling action still can’t implemented perfectly. The employee’s performance in Ledo Sub-District Office Bengkayang Regency is still not too good and still can’t make satisfaction. This can be seen clearly from the completion of the work which is not on time, unsatisfactory work result and lack of the provision of public services. Plus limited and minimum facilites making it difficult for the employees to finish their work.Keywords : Leadership Style and Performance